Subjective experience and perception of urban-inland blue spaces in urban parks and individual well-being: evidence from Xi’an, China - Wang, Lixin; Md. Sani, Norazmawati; Wang, Yuan; Xie, Xinrong; Zhang, Xiaoxiao; Sun, Daoyang; Zhang, Yanlong (Frontiers in Public Health, 2025)
IntroductionThe benefits of urban blue spaces in promoting health and well-being have been confirmed by a growing body of research. However, existing relevant studies mostly focus on objective proximity or accessibility and underestimate subjective experience and perception. Therefore, the aim of this study was to investigate the relationship between subjective experience and perception of blue spaces and human health in inland urban public parks.MethodsTo fill this gap, we conducted a field survey of five selected urban-inland public parks with blue spaces in Xi’an, to examine the association of subjective experience of urban-inland blue spaces in parks in terms of their quality, attraction, facility, and management, as well as individual well-being, and to identify the mediating role of subjective perception indicators in terms of social interaction, environmental improvement, recreational activity, and emotional recovery in the relationship.ResultsThe study collected 429 valid samples through field surveys and questionnaires, and adopted structural equation modeling to further validate the relationship between subjective experiences and perceptions of urban-inland blue spaces in public parks and individual well-being. The results suggest a potential mediating pathway, and that the quality of urban-inland blue space in parks significantly contributes to well-being outcomes. In addition, indirect pathways have significant associations with outcome variables mainly through subjective perception indicators of pollution reduction and exercise activity.DiscussionAlthough this study employed a cross-sectional design and self-reported data, which may impose limitations on causal inference and introduce potential biases. The findings of the study emphasize the importance of the subjective experience and perception of urban-inland blue space in public parks, enriching the evidence on urban-inland blue space planning and public health policymaking.